Successful Feasibility Human Trial of a New Self-Expandable Percutaneous Pulmonary Valve (Pulsta Valve) Implantation Using Knitted Nitinol Wire Backbone and Trileaflet α-Gal–Free Porcine Pericardial Valve in the Native Right Ventricular Outflow Tract. (June 2018) - Kim, Gi Beom; Song, Mi Kyoung; Bae, Eun Jung; Park, Eun-Ah; Lee, Whal; Lim, Hong-Gook; Kim, Yong Jin
Abstract : Background—: Self-expandable percutaneous pulmonary valve implantation (PPVI) for native right ventricular outflow tract lesions is still in the clinical trial phase. The aim of this study is to present the result of feasibility study of a novel self-expandable knitted nitinol wire stent mounted with a treated trileaflet α-Gal–free porcine pericardial valve for PPVI. Methods and Results—: A feasibility study using Pulsta valve (TaeWoong Medical Co, Gyeonggi-do, South Korea) was designed for patients with severe pulmonary regurgitation in the native right ventricular outflow tract, and 6-month follow-up outcomes were reviewed. Ten tetralogy of Fallot patients were enrolled. Before PPVI, severe pulmonary regurgitation (mean pulmonary regurgitation fraction, 45.5%±7.2%; range, 34.9%–56%) and enlarged right ventricular volume (mean indexed right ventricular end-diastolic volume, 176.7±14.3 mL/m 2 ; range, 158.9–205.9 mL/m 2 ) were present. The median age at PPVI was 21.7±6.5 years (range, 13–36 years). Five patients were successfully implanted with 28 mm and the other 5 with 26 mm valves loaded on the 18F delivery cable. No significant periprocedural complications were noted in any patient. At the 6-month follow-up, indexed right ventricular end-diastolic volume was dramatically decreased to 126.3±20.3 mL/m 2 (range, 99–164.2 mL/m 2 ), and the mean value of peak instantaneous pressure gradient between the right ventricle and the pulmonary artery decreased from 6.8±3.5 mm Hg (range, 2–12 mm Hg) before PPVI to 5.7±6.7 mm Hg (range, 2–12 mm Hg) without significant pulmonary regurgitation. There was no adverse event associated with the valve. Conclusions—: A feasibility study of the Pulsta valve for native right ventricular outflow tract lesions was completed successfully with planned Pulsta valve implantation and demonstrated good short-term effectiveness without serious adverse events. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02555319.